2021
DOI: 10.18510/hssr.2021.9247
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Ideological Constructions Embedded in English Textbooks: A Critical Discourse Perspective

Abstract: Purpose of the study: The subject study aims at investigating the construction of diverse ideologies embedded within English textbooks used in Pakistani settings at the elementary level. The entire study is based on a comparative analysis of English textbooks of Punjab Textbook Board (PTB) and Oxford University Press (OUP) and employs a critical discourse lens for a comprehensive analysis. Methodology: Based on purposeful sampling, the study hinges on insights of Critical Discourse Studies. Out of variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Ulum and Köksal (2019) have said that although culture has been the most prevalent factor in globally and locally written textbooks, particular ideologies are often infused with implicit or explicit biases. Afzal et al (2021) have revealed how the PTB English textbook authors in Pakistan have attempted to present a particular religion as the dominant religion of the country, concentrating particularly on the ideology of Pakistan. Tafazoli and Egan (2022) have proposed that curriculum and textbook designers must ensure that their own cultures are preserved through textbooks while incorporating maximized constructivist opportunities.…”
Section: Resultsmentioning
confidence: 99%
“…Ulum and Köksal (2019) have said that although culture has been the most prevalent factor in globally and locally written textbooks, particular ideologies are often infused with implicit or explicit biases. Afzal et al (2021) have revealed how the PTB English textbook authors in Pakistan have attempted to present a particular religion as the dominant religion of the country, concentrating particularly on the ideology of Pakistan. Tafazoli and Egan (2022) have proposed that curriculum and textbook designers must ensure that their own cultures are preserved through textbooks while incorporating maximized constructivist opportunities.…”
Section: Resultsmentioning
confidence: 99%